Verbinder aus Kunstharzpressholz mit erhöhter Reibung in der Scherfuge - Aurand, Simon (Karlsruher Berichte zum Ingenieurholzbau, 2023)
For the first time new connectors were realized using densified veneer wood (DVW). Initially, the DVW surface was modified to increase the friction between the connector and the timber part in the shear plane and thus significantly increase the load-carrying capacity of the connection. Friction tests were carried out to determine the friction coefficients of the surfaces. Based on the friction tests, the behavior of the surfaces in combination with inclined screws was investigated.